Bilateral Selective Laryngeal Reinnervation for Bilateral Vocal Fold Paralysis in Children - Lee, Janet W. (JAMA Otolaryngol Head Neck Surg, 2020)
IMPORTANCE: Bilateral vocal fold paralysis (BVFP) in pediatric patients is a challenging entity with multiple causes. Traditional approaches to managing BVFP include tracheostomy, arytenoidectomy, suture lateralization, cordotomy, and posterior cricoid enlargement. These interventions are used to create a stable airway but risk compromising voice quality. OBJECTIVES: To assess the use of bilateral selective laryngeal reinnervation (SLR) surgery to manage BVFP and restore dynamic function to the larynx in pediatric patients. DESIGN, SETTING, AND PARTICIPANTS: In this case series performed at 2 tertiary care academic institutions, 8 pediatric patients underwent bilateral SLR to treat BVFP (5 patients with iatrogenic BVFP and 3 with congenital BVFP) from November 2004 to August 2018 with follow-up for at least 1.5 years. INTERVENTIONS: Bilateral selective laryngeal reinnervation surgery. MAIN OUTCOMES AND MEASURES: Flexible laryngoscopy findings, subjective and objective measures of voice quality, subjective swallowing function, and decannulation in patients who were previously dependent on a tracheostomy tube. RESULTS: Participants included 6 boys and 2 girls with a median age of 9.3 (range, 2.2 to 18.0) years at the time of surgery. All 8 patients were decannulated; 6 patients had preoperative tracheostomies and 2 had perioperative tracheostomies. Voice quality, as measured using the GRBAS (grade, roughness, breathiness, asthenia, strain) scale, improved in 6 of 8 patients after reinnervation, and swallowing was not impaired in any patients. In 2 patients, GRBAS scale scores remained the same before and after surgery. Inspiratory vocal fold abduction was observed on both sides in 5 patients and on 1 side in 2 patients, with no active abduction observed in 1 patient. The follow-up period was more than 5 years in 7 of 8 patients and at least 1.5 years in all patients. CONCLUSIONS AND RELEVANCE: Bilateral SLR appears to be a promising treatment option for children with BVFP; it is currently the only option, to our knowledge, with the potential to restore abductor and adductor vocal fold movement. In patients with complete paralysis, this procedure may provide a strategy for airway management and restoration of the dynamic function of the larynx. It could be considered as a first-line technique before endolaryngeal or airway framework procedures, which carry a risk of compromising voice quality.